Synthesis, characterization, and antioxidant activity of some new N4-arylsubstituted-5-methoxyisatin-β-thiosemicarbazone derivatives - Muğlu, Halit (Springer Science and Business Media LLC, 2020)
Firstly, thiosemicarbazides were prepared by the reaction of hydrazine monohydrate with isothiocyanates in cold dry ethanol at 0 °C for 1 h. After that, new isatin-β-thiosemicarbazones were synthesized by treatment of 5-methoxyisatin with thiosemicarbazides in aqueous ethanol containing one drop of hydrochloric acid at reflux for 3 h. The chemical structures of products were confirmed by means of IR, 1H NMR, and 13C NMR data and by elemental analysis. All the synthesized compounds were evaluated for their antioxidant activity by 1,1-diphenyl-2-picryl hydrazyl (DPPH) radical scavenging method. The synthesized molecules showed lower antioxidant activity than the standard Trolox (8.757 μM). IC50 values of the newly synthesized isatin-β-thiosemicarbazone derivatives ranged from 12.455 to 73.471 μM.
Keywords: 3. Good health